Komunikasi Dakwah Digital dalam Penguatan Moderasi Beragama - Rohmah, Farikha; Jannah, Siti Raudhatul; Wazis, Kun (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2024)
The purpose of this study is to describe how preachers use digital communication technology in strengthening religious moderation and preachers' efforts to take opportunities and face challenges in strengthening religious moderation through digital da'wah communication. This study uses qualitative research method through library studies. The data this study were obtained from various literature such as books, journals, and other relevant documents. The results of study strengthening religious moderation through digital da'wah communication, preachers must choose right digital platform, create interesting, interactive, maintain credibility contents of the da'wah message, and increase accessibility of information. Efforts of preachers facing opportunities and challenges, namely understanding audience, optimizing digital media, anticipating flood information, focusing on substance the message, and discussing and meeting with the community. The implications this study are new knowledge for preachers in preaching in digital era and increasing ability of preachers using digital media to provide strengthening religious moderation to community.